HAKIKAT FUNGSI INTERMEDIASI PERBANKAN SYARIAH: STUDI KASUS DI KOTA BANDA ACEH - Ratna Mutia; Khairul Aswadi; Martahadi Martahadi (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2017)
In the economy of a country, banks have a very important role in facilitating the surplus party with a deficit of funds. This study aims to determine the effect of third party funds (DPK), non-performing financing (NPF) on financing to deposit ratio (FDR) in sharia banking in Banda Aceh City. This study uses secondary data in the form of time series using monthly data during the period 2010-2016, which is analyzed by using multiple linear regression methods. The results show that there is an influence of DPK on FDR, while NPF does not affect FDR on sharia banking. While simultaneously, these two variables have a significant effect on the intermediation function of sharia banking in Banda Aceh City. To be able to maintain its existence, sharia banking must be able to improve the service to the community, either in collecting DPK or in channeling the financing, so that it can perform its intermediation function well. However, this research has limitations in analyzing the intermediation function of sharia banking, which does not assess short-term mismatch (STM). Because the ratio of STM is what distinguishes the performance of liquidity between sharia and conventional banking.